Exploring the Definition of Sense of School Belonging in Schools with Female Teachers Outnumbering - Rasullu, Sarvan (ADA University, 2023)
This research aims to explore how teachers and male students define a sense of school belonging. In particular, the research focused on high school male students’ sense of school belonging at public schools where most teachers are females. Furthermore, the study also aimed to identify teacher qualities contributing to the definition of a sense of school belonging. The following research questions guided the study. 1. “How do teachers and male students define the role of male teachers in shaping a sense of school belonging?” 2. “What teacher qualities contribute to the definition of a sense of school belonging?” As a theoretical framework, the study used Lazarsfeld and Merton’s (1954) theory of homophily. A qualitative exploratory research design was employed to investigate boys’ sense of school belonging in an environment where female teachers outnumbered male teachers. The study was conducted in two public schools in Baku, which were selected through convenience sampling. Accordingly, the data were collected employing qualitative research methodologies with the help of semi-structured individual interviews with students and teachers. Ten student and six teacher participants were included. The findings of the study show that the sense of school belonging is consistent with the theory of homophily such as gender and age factors play a significant role in students’ sense of school belonging. However, due to the lack of exposure to male teachers, male students find it difficult to say how it would contribute to their definition of a sense of school belonging.
Keywords: Belonging (Social psychology) -- Education; Male teachers -- Influence; Teacher-student relationships -- Azerbaijan; Education